2022
DOI: 10.1007/s10340-022-01550-z
|View full text |Cite
|
Sign up to set email alerts
|

Resistant cassava cultivars inhibit the papaya mealybug Paracoccus marginatus population based on their interaction: from physiological and biochemical perspectives

Abstract: Dangerous Paracoccus marginatus papaya mealybugs cause considerable threats and challenges to cassava production and processing. The deployment of resistant cultivars offers effective, economical and eco-friendly management strategies for pest management. We utilized P. marginatus mortality, development and reproduction to evaluate the resistance of fteen cassava cultivars and conducted physiological and biochemical analyses when P. marginatus was fed on two resistant cultivars (Myanmar, C1115) and three susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…Although the defensive mechanisms activated in plants to defend against mealybugs are poorly known, a previous study showed that several cassava cultivars increased the activity of antioxidant enzymes when they were infested by the papaya mealybug Paracoccus marginatus (Chen et al, 2022). These enzymes protect the cells from oxidative stress (Alscher et al, 2002;Wang et al, 2018) and play a significant role in controlling the level of ROS from all organisms that live in the presence of oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the defensive mechanisms activated in plants to defend against mealybugs are poorly known, a previous study showed that several cassava cultivars increased the activity of antioxidant enzymes when they were infested by the papaya mealybug Paracoccus marginatus (Chen et al, 2022). These enzymes protect the cells from oxidative stress (Alscher et al, 2002;Wang et al, 2018) and play a significant role in controlling the level of ROS from all organisms that live in the presence of oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Although honeydew reportedly contains a high diversity of proteins (Sabri et al, 2013;Urbaneja-Bernat et al, 2023;Zhu et al, 2020), to our knowledge, the effects of herbivore-induced plant proteins in honeydew on the fitness of natural enemies remain unknown. Some of these plant proteins could be antioxidant enzymes, such as superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), glutathione Stransferase (GST) and polyphenol oxidase (PPO), among others, which are upregulated in plants when attacked by phloem feeders (Chen et al, 2022). If such proteins would contribute to enhanced fitness of natural enemies feeding on honeydew, this could be viewed as an indirect plant defence mechanism mediated by herbivore-induced plant proteins excreted in honeydew, although herbivores would be expected to be under selection to minimize excretion of such proteins in the honeydew.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results mentioned above can also be found in several pest–crop interaction studies, i . e ., cotton genotype and silverleaf whitefly ( Miyazaki et al., 2013 ), cassava varieties and papaya mealybug ( Paracoccus marginatus ) ( Chen et al., 2022b ) or T. cinnabarinus ( Lu et al., 2017 ), rubber tree germplasms, and Eotetranychus sexmaculatus ( Lu et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%